2017
DOI: 10.18203/2394-6040.ijcmph20174246
|View full text |Cite
|
Sign up to set email alerts
|

A study of treatment compliance of dog bite cases reporting to anti-rabies clinic of M.K.C.G Medical College, Odisha, India

Abstract: Background: Rabies a dreadful disease can easily be prevented by immediate wound care, vaccination and immunoglobin administration. Prognosis depends on the promptness of initiation, regularity and completion of treatment, determined by patient’s compliance. It partly depends on the patience and devotion of doctor for counselling the patient. The objectives of the study were to assess the treatment compliance of dog bite cases attending tertiary care centre for post exposure prophylaxis (PEP) of Rabies. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In this study, cases of animal bites were more in males than females, similar to findings of Sharma et al 7 We also found that the majority of patients that is 89% were exposed to dog bites, similar to the findings of Karmakar et al and Nishant et al but more than findings by Gadapani et al [8][9][10] In our study, lower limb was the most commonly injured site in 59.3% patients and similar findings were observed in a study conducted by Domple et al 11 In the present study, 45 (15.7%) patients did not wash wound after bite as compared to study by Kawale et al where 3206 (53%) did not manage their wound. 12 In our study, it was seen that 78% of patients completed all doses of ARV which was similar to findings of Lilare et al and Jena et al 6,13 The compliance to ARV in our study was more than findings by Nishant et al , Titoria et al and Praveen et al 9,14,15 Compliance to RIG in our study was 63.3% which is in accordance with findings by Kawale et al and Datta et al 12,16 There was significant association between compliance to ARV last dose with the type of animal. Similar results were found in a study conducted by Shivasakthimani et al and Wadde et al 17,18 There was significant association found between compliance to RIG with gender, socioeconomic status, type of animal and type of wound.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, cases of animal bites were more in males than females, similar to findings of Sharma et al 7 We also found that the majority of patients that is 89% were exposed to dog bites, similar to the findings of Karmakar et al and Nishant et al but more than findings by Gadapani et al [8][9][10] In our study, lower limb was the most commonly injured site in 59.3% patients and similar findings were observed in a study conducted by Domple et al 11 In the present study, 45 (15.7%) patients did not wash wound after bite as compared to study by Kawale et al where 3206 (53%) did not manage their wound. 12 In our study, it was seen that 78% of patients completed all doses of ARV which was similar to findings of Lilare et al and Jena et al 6,13 The compliance to ARV in our study was more than findings by Nishant et al , Titoria et al and Praveen et al 9,14,15 Compliance to RIG in our study was 63.3% which is in accordance with findings by Kawale et al and Datta et al 12,16 There was significant association between compliance to ARV last dose with the type of animal. Similar results were found in a study conducted by Shivasakthimani et al and Wadde et al 17,18 There was significant association found between compliance to RIG with gender, socioeconomic status, type of animal and type of wound.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in contrast with what has been generally observed before, that is, that men are proportionally more affected than women. 18,19,20 The reasoning for this difference was not investigated in this study. Importantly, it is an indication for the need to analyse site-specific data to determine the risk groups and their characteristics which should not be universally accepted based on studies involving other study populations.…”
Section: Discussionmentioning
confidence: 88%
“…Dog bite surveys have been used to report on the epidemiology of dog bites, to determine the knowledge and practices (including adherence) for rabies PEP and to provide data for the estimation of human rabies cases. 18,19,20,21,22,23,24,25 In South Africa, active transmission cycles of the rabies virus in domestic dogs have been reported in the mid-20th century. 26 The history of dog rabies control in South Africa is characterised by intermittent success and also failures resulting in outbreaks and consequently also human cases.…”
Section: Introductionmentioning
confidence: 99%